Genotoxic activities of wastewater after ozonation and activated carbon filtration: Different effects in liver-derived cells and bacterial indicators. (1st November 2020) - Mišík, Miroslav; Ferk, Franziska; Schaar, Heidemarie; Yamada, Masami; Jaeger, Walter; Knasmueller, Siegfried; Kreuzinger, Norbert
Highlights: The impact of ozonation on cytotoxic/genotoxic properties of treated wastewater was studied. Ozonation induced mutagenic effects in highly sensitive repair deficient Salmonella tester strains. Ozonation reduced the genotoxic properties of wastewater in hepatoma cells. Ozonation did not lead to acute toxic effects. Ozonation may prevent genotoxic damage of wastewaters in higher organisms. Abstract: Aim of this study was to investigate the impact of advanced wastewater treatment techniques (combining ozonation with activated carbon filtration) on acute and genotoxic activities of tertiary treated wastewater. Concentrated samples were tested in Salmonella /microsome assays. Furthermore, induction of DNA damage was measured in liver-derived cells (human hepatoma and primary rat hepatocytes) in single cell gel electrophoresis experiments, which are based on the measurement of DNA migration in an electric field. These cell types possess phase I and phase II enzymes, which catalyze the activation/detoxification of mutagens. Acute toxicity was determined with the trypan blue exclusion technique. We found no evidence for mutagenic effects of non-ozonated samples in several bacterial tester strains (TA98, TA100, YG7108, YG7104, YG7112 and YG7113) but clear induction of His + mutants after O3 treatment in two strains with defective genes encoding for DNA repair, which are highly sensitive towards alkylating agents (YG7108 and YG7104). These effects were reduced after activated carbon filtration. Furthermore, we detected a slight increase of mutagenic activity in strain YG1024 with increased acetyltransferase activity, which is sensitive towards aromatic amines and nitro compounds in untreated water, which was not reduced by O3 treatment. A completely different pattern of mutagenic activity was seen in liver-derived cells; non ozonated samples caused in both cell types pronounced DNA damage, which was reduced (by ca. 25%) after ozonation. Activated carbon treatment did not cause a substantial further reduction of DNA damage. Additional experiments with liver homogenate indicate that the compounds which cause the effects in the human cells are promutagens which require enzymatic activation. None of the waters caused acute toxicity in the liver-derived cells and in the bacterial indicators. Assuming that hepatic mammalian cells reflect the genotoxic properties of the waters in vertebrates (including humans) more adequately as genetically modified bacterial indicators, we conclude that ozonation has beneficial effects in regard to the reduction of genotoxic properties of treated wastewaters. Graphical abstract: Image, graphical abstract